Association Between Educational Attainment and Chronic Pain: A Mediation Mendelian Randomization Study - Wang H; Liu M; Li H; Xu S (Journal of Pain Research)
Hanqi Wang, Mingjuan Liu, Hongbo Li, Shijie Xu Department of Anesthesiology and Pain Research Center, The First Hospital of Jiaxing University, Jiaxing, People’s Republic of ChinaCorrespondence: Hanqi Wang, Department of Anesthesiology and Pain Research Center, The First Hospital of Jiaxing University, Jiaxing, People’s Republic of China, Tel +86 19517900056, Email 764847739@qq.comBackground: The underlying association between educational attainment (EA) and chronic pain (CP) risk is not clear. This study aimed to investigate the causal relationship of EA with CP using Mendelian randomization (MR).Methods: Single nucleotide polymorphisms (SNPs) for EA were selected from the Social Science Genetic Association Consortium (SSGAC). Inverse-variance weighted (IVW), weighted median, penalized weighted median, maximum likelihood (ML), and MR-Egger methods were used to estimate causal effects. Two sample MR analyses were undertaken to assess whether EA has a causal effect on CP. We also performed mediation analyses to estimate the mediation effects.Results: A genetically predicted higher EA was associated with a decreased risk of multisite chronic pain (MCP) (odds ratio [OR] = 0.772, 95% confidence interval [CI] 0.732– 0.816 per one standard deviation of longer education, P < 0.05), and the Genome-wide association studies (GWAS) data for chronic widespread pain (CWP) supported the result mentioned above. Potential mediators included body mass index (BMI) (OR = 1.176, 95% CI 1.091– 1.267, P < 0.05), smoking (OR = 1.054, 95% CI 1.028– 1.081, P < 0.05), and depression (OR = 1.201, 95% CI 1.147– 1.258, P < 0.05) have all been proven to be causally associated with MCP. The proportions of the effects of genetically predicted EA mediated through genetically predicted BMI, smoking, and depression were 17.1%, 23.6%, and 9.2%, respectively.Conclusion: Genetically predicted higher educational attainment reduces multisite chronic pain risk, partially mediated by body mass index (17.1%), smoking (23.6%), and depression (9.2%), highlighting education’s protective role and its potential in chronic pain prevention strategies. Keywords: educational attainment, chronic pain, Mendelian randomization, risk factors